Successful Treatment of Invasive Mucormycosis in Orthotopic Liver Transplant Population - Taryn A. Eubank; Constance M. Mobley; Mozhgon Moaddab; Mark J. Hobeika; Melissa O’Neal; William L. Musick; Joshua M. Knight; Joseph S. Galati; Sudha Kodali; Akshay Shetty; David W. Victor; Ashish Saharia; et al. (Case Reports in Transplantation)
Mucormycosis is caused by ubiquitous fungi and encompasses a variety of different opportunistic syndromes in humans that disproportionately affect immunocompromised patients. Mortality has been documented to range between 50 and 100%; however, location of infection greatly dictates likelihood of survival. Treatment of mucormycosis involves aggressive surgical intervention and combination therapy of antifungal agents. In solid organ transplant recipients, immunosuppressive agents used to prevent rejection of the transplanted organ pose additional obstacles in the treatment of invasive fungal infections. We report on 3 high models for end-stage liver disease (MELD-Na) score orthotopic liver transplant (OLT) recipients who all were diagnosed with Rhizopus spp. infections with positive, 1-year outcomes after aggressive, individualized treatment.